User interface analysis on shopee website using heuiristic method - Zeinor Rahman; Budyi Suswanto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Human and computer interaction is a science that focuses on planning and designing a system so that users can interact and work together according to the needs of the users themselves in the most effective way at every step of their work. The role of the user interface greatly influences the usability of an application or system. Heuristic Evaluation (HE) is considered the best usability evaluation method compared to others because it can find severe problems that other methods cannot detect. Therefore researchers will analyze the user interface on the Shopee website using the HE method. User Interface Analysis on Websites with the HE Method through online questionnaire distribution, from the results of online questionnaire distribution, it can be concluded that the website has deficiencies in terms of auxiliary features and documentation to assist users in using the system. Declared less because it has the lowest rcount (Total) value of 0.587 compared to other counts. Suggestions for research on Shopee user satisfaction analysis using the HE method, the authors convey suggestions that need to be improved in future research, namely that it is necessary to conduct research on Shopee user satisfaction using the HE method in a broader scope.